NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL RANAH TIGA WARNA KARYA A. FUADI - Dwi Silviyani; Hasanuddin .; Ermanto . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This research is conducted base on background, that is, moral less of young generation until the generation should have characters. Novel of Ranah Tiga Warna by A. Fuadi describes human who have specific characteristics, such as character of education. The character is shown on speech, behavior, and story of narrator on the novel. This research tends to qualitative approach with content analysis method. The result of this study is five values of education character in the novel of Ranah Tiga Warna by A. Fuadi there are believing and praying for God, truthiness, smartness, strongly, carefully. Kata kunci: nilai, pendidikan karakter, novel, Ranah Tiga Warna